EFFICENCY OF MARKETING OF THE TABLE EGGS IN THE PRIVATE SECTOR IN PROVINCE OF BAGHDAD IN 2015 - & Thamer, Bdeawe (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The study aims to measure the marketing margins and costs and the marketing efficiency of the table eggs were produced by the privete sector in Baghdad province, and to achive the study aims we design questionnaire are for the three marketing levels in marketing path : producer , wholsale trader and retailer trader. The results showed that share of produce which paid by consumer was (82%) as a one of indicators of high marketing efficiency , the producer prof it was about (68%), and profit of the wholesale trader about (18%), and profit of retailer profit about (14%). The study estimate the relative importance of item of the marketing margin between producer and consumer , the relative importance of profits of wholesale trader came in first rank by about (%38.7) from item of the marketing margin between producer and consumer , and in the secord rank came the relative importance of profits of retailer trader by about (%29.9) from items of the marketing margin between producr and consumer , and in the third rank came the relative importance of marketing costs of the whole saler trader by about (%25.7) from item the marketing margin between the producer and consumer of ter them came the relative importance of marketing costs of the retailer trader by (%4.3) from items of the marketing margin , while the relative importance of the transportation costs came in the last rank about (%1.3) from itiems of the marketing margin between producer and consumer. Thr marketing efficiency of the table eggs were produced according to scale (1) about (%89.19) and according to scale (2) about (%72.14) and this indicate hight of the marketing efficiency of the table eggs produced by private sector in Baghdad province according the two sacles .the study reached to some recommoudations such as providing the vechiles to transport the table eggs from producing points to marketing points which have airconditionrs to reduce the waste and damage of eggs during the marketing services, and providing producing equipmeyts and the agricultural marketing equipments of the table eggs by good quality and satible prices which has active role in decrease or increase the producing costs and agricultural marketing.